In situ layered double hydroxide for efficient remediation of acidic water - Qian, Zhongyang; Hu, Jiaojing; Chao, Jingbo; Huang, Jinlou; Coulon, Frederic; Zhang, Jingqi; Hu, Qing; Yang, Xiao Jin (Wiley, 2025)
The efficient and sustainable in situ remediation of high‐strength acidic groundwater contaminated by complex micropollutants with minimal use of chemicals is a challenge. Here it is reported that MgAl alloy achieves neutralization and a complete removal of 20 mg L−1 Cd2+, Cr(VI), Cu2+, Ni2+, and Zn2+ in 15 min from acidic water free of chemicals. The removal rate of heavy metals and nitrate increases with decreasing pH and is not significantly reduced after 5 cycles of treating acidic water. The excellent performance of MgAl alloy in reactivity, durability, and efficiency is attributed to a synergistic effect of chemical reduction and eutectic reactions, which is catalyzed by intermetallic compound Mg17Al12 and in situ layered double hydroxide (iLDH). The pH 2.47 of an acid mine drainage sample from copper ore mines is raised to 7.4 ± 0.4 and the concentrations of Al, Cr, Cu, Fe, Mn, Ni, and Zn ions are reduced to <0.55 mg L−1 from 5–559 mg L−1. In contrast, quick lime treatment increases the pH to 12.45, whereas activated carbon, zerovalent iron, and conventional LDH are not able to neutralize or remove Al3+ and heavy metals. The findings of this study provide new insights into the efficient, green, and sustainable approach for acidic water remediation.
Keywords: 3304 Urban and regional planning; 4101 Climate change impacts and adaptation; 4104 Environmental management